(untitled) (EAAE Annual Conference Proceedings, 2023)
At a recent Digital-Live-Design conference (2021), bringing together Swiss art curator, critic and art historian Hans-Ulrich Obrist, Malian writer, film director, and cultural theorist Manthia Diawara and German author, producer and filmmaker Alexander Kluge, the discussion of the need for a New European Bauhaus for this century was addressed. One of the leading intellectual voices in Germany, Kluge specified that a new Bauhaus should not be “so rational and geometric as the historic Bauhaus.” Sparked by his cooperation with Diawara, Kluge made an appeal for a “European-African Bauhaus” in order “to rebuild our lives.”